2021
DOI: 10.1186/s12889-021-11811-8
|View full text |Cite
|
Sign up to set email alerts
|

Legal status as a life course determinant of health: parent status, adjudication stages, and HIV knowledge among highlanders in Thailand

Abstract: Background Rising nativism and political volatility worldwide threaten to undermine hard-won achievements in human rights and public health. Risks are particularly acute for hundreds of millions of migrants, minorities, and Indigenous peoples, who face disproportionately high health burdens, including HIV/AIDS, and precarious legal status (LS). While LS is receiving increasing attention as a social determinant of health and HIV, understandings are still limited to select immigrant communities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This study broadens our understanding of statelessness and health in Canada by exploring the nexus between status and health as SPs age, consider life goals, and interact with immigration processes. Our participants’ experiences also illustrate that the legal statuses of stateless persons in Canada are not fixed but can change throughout life in both in situ and migratory contexts (Koning et al 2021). Our findings thus add statelessness to the corpus on non-citizen vulnerability in Canada and confirm that lack of nationality has egregious effects on health and well-being, in ways that mostly align with other non-citizen groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study broadens our understanding of statelessness and health in Canada by exploring the nexus between status and health as SPs age, consider life goals, and interact with immigration processes. Our participants’ experiences also illustrate that the legal statuses of stateless persons in Canada are not fixed but can change throughout life in both in situ and migratory contexts (Koning et al 2021). Our findings thus add statelessness to the corpus on non-citizen vulnerability in Canada and confirm that lack of nationality has egregious effects on health and well-being, in ways that mostly align with other non-citizen groups.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, statelessness negatively impacts a number of social determinants of health, including access to quality housing, sanitation, employment, and food security (Sköld 2023, 10–11). Koning et al (2021) find that precarious legal status is a dynamic determinant that affects health differently at various stages of nationality recognition. The COVID-19 pandemic also exposes links between legal status and health outcomes.…”
Section: Statelessness and Healthmentioning
confidence: 91%
“…Comparative research shows that individuals without official identity documents often come from marginalised communities (e.g. Cheva-Isarakul and Sperfeldt 2023 ; Liew 2021 ; Pearson 2021 ; Sardelić 2021 ; Sperfeldt 2020 ) or live in zones without effective state institutions (Koning et al 2021 ; Lee and Zhang 2017 ; Adamczyk and Doumit 2024 ; Harbers 2020 ). This creates a vicious cycle as vulnerable individuals are rendered even more vulnerable by their lack of state-recognised documents.…”
Section: Introductionmentioning
confidence: 99%
“…Their possession, therefore, demarcates the scope of geographic and social mobility ( Cheva-Isarakul, 2019 ). Studies using data from Thailand, for example, demonstrated that legal status (as indicated by the possession of identification cards) affects education and health risk ( Koning, Flaim, Baldiga, & Feingold, 2021 ), access to healthcare ( Flaim et al, 2021 ; Herberholz, 2020 ), as well as access to land and credit ( Flaim, Williams, & Ahlquist, 2019 ), that is, more generally, the key factors that matter for social ascent. Experiences of in situ stateless populations in Southeast Asia further showed that protracted statelessness results in an intergenerational transmission of immobilization ( McAuliffe, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of in situ stateless populations in Southeast Asia further showed that protracted statelessness results in an intergenerational transmission of immobilization ( McAuliffe, 2017 ). Koning et al (2021) , for example, found that parent citizenship increases the odds of greater adult HIV knowledge, which is partially explained by birth registration, adult citizenship and secondary school completion.…”
Section: Introductionmentioning
confidence: 99%